Pengaruh Penambahan Tepung Temulawak (Curcuma xanthoriza) Dalam Ransum Terhadap Performa Produksi Ayam Kampung Unggul Balitnak - Trisno Agung Wibowo; Novi Eka Wati; Miki Suhadi (Wahana Peternakan, 2020)
The aim of the study was to know the effect of Curcuma xanthorhiza as herbal feed additive on feed consumption, daily body weight gain and feed conversion ratio of Kampung Unggul Balitnak (KUB) Chicken. The research was conducted at Kemukus Village, Ketapang District, South Lampung Regency. The experimental used 80 unisex KUB chicken aged 5 week. They were feed a ration with control ration + 0% temulawak flour (P0), control ration + 0,1% temulawak flour (P1), control ration + 0,2% temulawak flour (P2) and control ration + 0,3% temulawak flour (P4) during 30 days. The control ration containing 21% crude protein and 3150 kcal/kg metabolism energy. The study used a quantitative method with completely randomized design with 4 treatments and 4 replications. The results showed that the addition of temulawak flour (Curcuma xanthoriza) up to 0.3% did not effect (P> 0.05) on feed consumption but was affected (P <0.05) on daily body weight gain and feed conversion ratio. Keywords: daily body weight gain, feed consumption, feed conversion ratio, KUB Chicken, temulawak